From Chaos to Clarity: How Graphic Organizers Shape EFL Descriptive Writing - Erniwati Erniwati (Interference: Journal of Language, Literature, and Linguistics, 2026)
Abstract. Writing in English as a foreign language (EFL) involves complex linguistic, cognitive, metacognitive, and affective processes that often challenge learners in organizing ideas, maintaining coherence, and managing the writing process effectively. This study aims to examine the theoretical and pedagogical contributions of the Cookie Comprehension and Composition Graphic Organizer (3CGO) in improving EFL students’ descriptive writing skills. The study employed a qualitative library research design through a literature review approach. Data were collected using document analysis from scholarly journal articles, books, conference papers, and theses published between 2014 and 2025, retrieved from academic databases including ERIC, Google Scholar, and ResearchGate. The collected literature was analyzed thematically by categorizing findings into cognitive, metacognitive, linguistic, and affective dimensions of EFL writing. The findings reveal that the 3CGO serves as an integrated visual and metacognitive framework that helps students organize ideas systematically, connect reading comprehension with writing production, develop vocabulary and coherence, and regulate their writing processes through planning, monitoring, and evaluation. The organizer also reduces writing anxiety by providing learners with a clear structural pathway for composing texts. The novelty of this study lies in its conceptualization of the 3CGO not merely as a brainstorming tool, but as a comprehension-to-composition framework that simultaneously supports language development, cognitive processing, learner autonomy, and emotional engagement in EFL writing. Grounded in constructivist and self-regulated learning theories, the study highlights the broader global implications of integrating visual and metacognitive scaffolding into EFL pedagogy to foster reflective, confident, and independent writers across diverse language-learning contexts. Keywords: 3CGO, Descriptive writing, EFL writing, Graphic organizers, Metacognitive strategies